A Study of Mongolian and Tibetan Texts of the Poem “No Trust Such as Entrusting” Written by Noyon Khutugtu - Dashnyam, Munkh-Otgon (Tibetan Studies, 2024)
Not few years have been passing hence the foreign as well as domestic scholars and researchers are being studied and interested in the literary works written by Gobi’s King Reincarnate Danzanravjaa. One can say that the study of poems and other literary works written in the Mongolian language by the Reincarnate had developed in a comparatively wide range. But the study of works written in the Tibetan language is not so progressive as would like. In this connection, it is worth mentioning that the study of several literary works that exist in the Mongolian and Tibetan languages is extremely rare and scarce. Therefore, in this article, we tried to narrate the general study review of works by King Reincarnate that do exist in the Mongolian and Tibetan language versions, as well as the Mongolian and Tibetan texts of one work that has been found recently, and their correlations, distinctions, disrepancies and others based on concrete examples. Ноён хутагтын “Итгэмжлэх мэтийн итгэл үгүй” шүлгийн монгол төвөд эхүүдийн судалгаа Хураангуй: Говийн ноён хутагт Данзанравжаагийн зохиол бүтээлийг гадаад дотоодын эрдэмтэн судлаачид сонирхон судалж эхэлсээр багагүй хугацаа өнгөрч байна. Хутагтын монгол хэлээрх шүлэг зохиолын судалгаа нь харьцангуй өргөн дэлгэр хөгжсөн гэхэд болох бөгөөд харин төвөд хэлээрх бүтээлийн судалгаа нь төдийлөн ахицтай биш байгаа юм. Үүнтэй уялдаад монгол төвөд хоёр хэлээр байдаг хэд хэдэн зохиолын судалгаа нь ч туйлын ховор хомс гэж хэлж болно. Тиймээс энэхүү өгүүлэлд Ноён хутагтын монгол төвөд хоёр хэлээр байдаг зохиолуудын судалгааны ерөнхий тойм хийгээд түүний дээр саяхан шинээр олдсон нэгэн зохиолын монгол төвөд эх бичгүүд, тэдгээрийн харьцаа, ялгаа зөрөө зэргийг жишээлэн өгүүлэхийг зорилоо. Түлхүүр үг: Ноён хутагт, монгол төвөд эх бичиг, хуулбар, хувилбар